Syrian Hamsters (Mesocricetus auratus) Oronasally Inoculated With a Nipah Virus Isolate From Bangladesh or Malaysia Develop Similar Respiratory Tract Lesions. (January 2015) - Baseler, L.; de Wit, E.; Scott, D. P.; Munster, V. J.; Feldmann, H.
Nipah virus is a paramyxovirus in the genus Henipavirus, which has caused outbreaks in humans in Malaysia, India, Singapore, and Bangladesh. Whereas the human cases in Malaysia were characterized mainly by neurological symptoms and a case fatality rate of ∼40%, cases in Bangladesh also exhibited respiratory disease and had a case fatality rate of ∼70%. Here, we compared the histopathologic changes in the respiratory tract of Syrian hamsters, a well-established small animal disease model for Nipah virus, inoculated oronasally with Nipah virus isolates from human cases in Malaysia and Bangladesh. The Nipah virus isolate from Bangladesh caused slightly more severe rhinitis and bronchointerstitial pneumonia 2 days after inoculation in Syrian hamsters. By day 4, differences in lesion severity could no longer be detected. Immunohistochemistry demonstrated Nipah virus antigen in the nasal cavity and pulmonary lesions; the amount of Nipah virus antigen present correlated with lesion severity. Immunohistochemistry indicated that both Nipah virus isolates exhibited endotheliotropism in small- and medium-caliber arteries and arterioles, but not in veins, in the lung. This correlated with the location of ephrin B2, the main receptor for Nipah virus, in the vasculature. In conclusion, Nipah virus isolates from outbreaks in Malaysia and Bangladesh caused a similar type and severity of respiratory tract lesions in Syrian hamsters, suggesting that the differences in human disease reported in the outbreaks in Malaysia and Bangladesh are unlikely to have been caused by intrinsic differences in these 2 virus isolates.